2022
DOI: 10.1128/mbio.03497-21
|View full text |Cite
|
Sign up to set email alerts
|

Functional Irreplaceability of Escherichia coli and Shewanella oneidensis OxyRs Is Critically Determined by Intrinsic Differences in Oligomerization

Abstract: Evolution may drive homologous proteins to be functionally nonexchangeable in different organisms. However, much is unknown about the mechanisms underlying this phenomenon beyond amino acid substitutions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 48 publications
1
3
0
Order By: Relevance
“…Potential reasons for this observation include that multiple heme-trafficking proteins contribute to delivering heme to the CCM apparatus, that heme is mobilized independent of any heme-trafficking proteins, and that the aforementioned mechanisms work in combination. In addition to the cyt c content, the activity of catalase KatB, which is a Type I hemoprotein dictating H 2 O 2 degradation in S. oneidensis ( 43 ), was also subjected to regulation of HtpA. Our findings are in line with the proposal that the assembly of catalase in vivo is assisted by chaperones ( 55 ), albeit such proteins had not been identified.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Potential reasons for this observation include that multiple heme-trafficking proteins contribute to delivering heme to the CCM apparatus, that heme is mobilized independent of any heme-trafficking proteins, and that the aforementioned mechanisms work in combination. In addition to the cyt c content, the activity of catalase KatB, which is a Type I hemoprotein dictating H 2 O 2 degradation in S. oneidensis ( 43 ), was also subjected to regulation of HtpA. Our findings are in line with the proposal that the assembly of catalase in vivo is assisted by chaperones ( 55 ), albeit such proteins had not been identified.…”
Section: Discussionsupporting
confidence: 83%
“…We then asked if HtpA delivers heme to Type I hemoproteins. We tested this notion with catalase KatB, which contains heme b and is the predominant enzyme for scavenging hydrogen peroxide (H 2 O 2 ) in the cell ( 41 - 43 ). The H 2 O 2 consumption assay revealed that the Δ htpA strain decomposed H 2 O 2 at a rate slower than WT ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…LTTRs are typically homotetrameric proteins ( 7 , 9 ), but this oligomeric state is not universal and some members of the family are found in lower (e.g., dimer) and higher (e.g., octamer) oligomeric states ( 9 , 14 , 33 , 34 ). Ligand binding was also shown to modulate the oligomeric state of some LTTRs ( 7 , 33 ).…”
Section: Resultsmentioning
confidence: 99%
“…To identify amino acid residues during complex formation, determine the types of interaction, and compile conformational maps, the software package "BIOVIA Discovery Studio" was used. The processes of visualization and clustering of obtained results were done with the help of FOREL algorithm-based program in Python environment due to the equation presented below:ΔGexp= -RT ln(1/K) (1)ΔG -Gibbs free energy, R -gas constant, Tabsolute temperature, K -binding constant[26].Statistical analyses:The carried-out experiments were done in 5 series with 3 repeats for each sample. For data analysis of all the TA new synthetic derivatives effects evaluation MS Excel tool was used.…”
mentioning
confidence: 99%